Tecnologia assistiva por idosos atendidos em serviços de saúde - Rodrigues, Tatyanni Peixoto (2017)
Introduction: Assistive Technology in the context of aging is a term scarcely used in Brazil, which covers a range of resources and services used to provide or enhance functional abilities of people with disabilities and/or elderly people, with a view to promoting quality of life and/or enabling them to achieve an active aging, with independence and social inclusion. Objectives: to identify the knowledge produced in the scientific literature about the contributions of Assistive Technology in maintaining the functionality of elderly people; to know the perception of elderly people about Assistive Technology; to identify the Assistive Technology used by elderly people from two cities in the state of Paraíba. Method: this is an exploratory research with mixed approach, which was performed in two cities of Paraíba: elderly people assisted in the Family Health Units, in João Pessoa/PB, and elderly people attending Peer Groups in the city of Cajazeiras/PB. The study was attended by 393 elderly people of both genders. Data collection took place in two stages: the first one was attended by 225 elderly people in 2011; and, in the second stage, 168 elderly people took part in 2014, from a semi-structured interview including the Free Word Association Test, with the inducting term: “assistive technology”, and sociodemographic data. The collected data were analyzed using the Categorical Thematic Content Analysis Technique subsidized by Bardin (2013) and the Textual Analysis with the help of the IRaMuTeQ software (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires), version 0.7 alpha 2. The research complied with the ethical and legal guidelines envisaged in Resolutions 196/96 and 466/12 of CNS/MS. Results and Discussion: the data collected in the two stages of this research gave rise to three papers presented in the results and discussion. The first paper: Influence of Assistive Technology in maintaining the functionality of the elderly person: Integrative Revision, where we noted the importance of the production of knowledge about Assistive Technology, which is a theme slightly explored in the scope of aging; second paper: Perception of elderly people assisted in family health units about Assistive Technology. We can observe that elderly people are aware of AT and describe some of the most well-known types, as well as perceive the importance of AT in the quality of life of the elderly person; and the third paper: Assistive Technology used by elderly people in two cities of Paraíba. We can observe that the elderly people from these two cities use Assistive Technology, although in a very incipient way, since there is a need for higher investments for the elderly person in the scope of public health policies. Final considerations: we have observed that AT is perceived by elderly people with an emphasis on resources. Concerning the use of AT by the surveyed population, the two cities highlighted the use of both services and resources in activities of daily living to improve quality of life and to promote inclusion of the elderly person, especially the elderly people suffering from chronic diseases. We should emphasize the need for more studies and research with Assistive Technology, particularly Gerontological Health and Nursing in the care of the elderly person, due to the benefits that the use of Assistive Technology entails for quality of life.